(untitled) (Research, Society and Development, 2021)
Objective: To understand the role of health professionals in Primary Health Care in relation to palliative care? Method: The study is an integrative literature review, with a qualitative approach, carried out by reviewing articles published in the database of the Virtual Health Library (VHL). The following descriptors were used on the basis of DeCS (Health Sciences Descriptors): Palliative Care; Nursing care; Primary Health Care. During the searches, 21 articles were found, of these, 8 were part of the study. The inclusion criteria were bibliographic searches published between the years 2002 to 2021. The exclusion criteria were articles that were not relevant to the theme of the study. Results: Quality of life is understood as the possibility of autonomy in relation to decision-making, as well as the minimization of pain and / or invasive procedures that cannot modify the process of dying with dignity. Bearing in mind that the principles of palliative care are the offer of quality of life and control of pain and suffering, it is understood that the multidisciplinary team of Primary Health Care needs to be trained to provide humanized palliative care in the patient’s home environment. Conclusion: The present has successfully achieved the objectives set regarding the contributions of the multidisciplinary team of Primary Health Care about Palliative Care aiming at better quality of care and comfort to the terminally ill patient. Thus, it becomes increasingly urgent to prioritize palliative care through Primary Health Care, enabling the organization, coordination and humanized assistance to the patient in their home bed.